Nature's Army : When Soldiers Fought for Yosemite - Meyerson, Harvey (Modern war studies, 2020)
"Despite the worldwide renown and popularity of Yosemite National Park, few people know that its first stewards were drawn from the so-called Old Army. From 1890 until the establishment of the National Park Service in 1916, these soldiers proved to be extremely competent and farsighted wilderness managers. Meyerson recaptures the forgotten history of these early environmentalists and shows how their work countered the army's Indian-fighting image and set significant standards for the future oversight of our national parks. This expanded paperback edition contains a foreword by Beth Bailey introducing the book to a new audience and explaining its importance to the field of military history. In his new preface, Meyerson discusses the book's origin and reception, provides a wealth of information on how the Army during this period sought to define its identity and purpose, and talks about the twenty-first-century National Park Service and how Yosemite ranger Shelton Johnson has almost single-handedly "rescued the army's role in the national parks from an obscure corner of history" by introducing park visitors and many others to the role of the African American soldiers who served in the park-troops of the Buffalo Soldiers, 9th Cavalry."--